(untitled) (Central Asian Journal of Medical Sciences, 2021)
Objectives: Our goal was to assess the outcomes of congenital primary hypothyroidism and evaluate forms of dysgenesis forms among children diagnosed with congenital primary hypothyroidism Methods: A cross-sectional study recruited all children diagnosed with congenital primary hypothyroidism between 2013 and 2020. All data, including demographic, clinical examination report, laboratory test results, and results of hand x-ray and ultrasound of thyroid glands, was collected from parents and medical records at hospitals. Results: Thyroid dysgenesis accounted for 76.3% of the causes of congenital primary hypothyroidism. Of all participants, 43% had an intellectual disability, and their average delayed bone age was 12.74 months. The most common abnormality of the thyroid gland was hypoplasia (76.3%). The age at diagnosis was the significant predictor for skeletal maturity delay (k = 0.25; 95% Cl = 0.17 - 0.33; p < 0.001) and for intellectual disability (a OR = 1.04; p < 0.004). Conclusions: Dysgenesis of the thyroid gland was the main cause of congenital hypothyroidism. Age of diagnosis of congenital primary hypothyroidism was a significant determinant of irreversible adverse later outcomes among children in Mongolia.